Overview of Chinese Characters Unique to Korea - Chang-joon, YOON (International Journal of Culture and History, 2024)
In this paper, the situation of Chinese characters unique to Korea made in Korea and used only in Korea was analyzed. Such a study will provide major information on how Korean ancestors used their unique Chinese characters and what contents the unique Chinese characters were intended to contain. This study is also expected to help the understanding of how Chinese characters were used in the different language environments for Korean and Chinese with different language systems from each other and how those meanings unique to Korea that could not be expressed in Chinese characters were written.